Biaxial quantification of deep layer transverse carpal ligament elastic properties by sex and region. (December 2016) - Mathers, Bryan; Agur, Anne; Oliver, Michele; Gordon, Karen
Abstract: Background: The transverse carpal ligament is a major component of the carpal tunnel and is an important structure in the etiology of carpal tunnel syndrome. The current study aimed to quantify biaxial elastic moduli of the transverse carpal ligament and compare differences between sex and region (Radial and Ulnar). Methods: Biaxial testing of radial and ulnar samples from twenty-two (thirteen male, nine female) human fresh frozen cadaveric transverse carpal ligaments was performed. Elastic moduli and stiffness were calculated and compared. Findings: Biaxial elastic moduli of the transverse carpal ligament ranged from 0.76 MPa to 3.38 MPa, varying based on region (radial and ulnar), testing direction (medial-lateral and proximal-distal) and sex. Biaxial elastic moduli were significantly larger in the medial-lateral direction than the proximal-distal direction ( P < 0.001). Moduli were significantly larger ulnarly than radially ( P = 0.001). No significant differences due to gender were noted. Interpretation: The regional variations in biaxial elastic moduli of the transverse carpal ligament may help improve non-invasive treatment methods for carpal tunnel syndrome, specifically manipulative therapy. The smaller biaxial elastic moduli found in the radial region suggests that manipulative therapy should be focused on the radial aspect of the transverse carpal ligament. The trend where female transverse carpal ligaments had larger stiffness in the ulnar location than males suggests that that the increased prevalence of carpal tunnel syndrome in women may be related to an increased stiffness of the transverse carpal ligament, however further work is warranted to evaluate this trend. Highlights: Biaxially tested transverse carpal ligament to determine mechanical properties. Biaxial elastic moduli greater in medial-lateral direction than proximal-distal Biaxial elastic moduli greater in ulnar region than in radial